(untitled) (Bangladesh Agronomy Journal, 2020)
The experiment was conducted to study the effect of biochar on growth and yield of sesame. In the experiment, the treatment consisted of three varieties, viz., V1 = BARI Til- 2, V2 = BARI Til-3 and V3 = BARI Til-4, and five levels of biocharviz., B0= control (no biochar application), B1= 2 t ha-1, B2= 4 t ha-1, B3= 6 t ha-1 and B4= 8 t ha-1. The experiment was laid out in two factors randomized complete block design (RCBD) with three replications.Variety, application of different levels of biochar and their interaction showed statistically significant variation in plant height, number of leaves plant-1at 55 and 80 DAS and at harvest, capsules plant-1, seeds capsule-1, 1000-seed weight, seed yield, stover yield, biological yield and harvest index.The highest plant height (70.34, 110.95 and 109.84 cm at 55 and 80 DAS and at harvest respectively), number of leaves plant-1 (80.47, 116.70 and 94.54 at 55, 80 DAS and at harvest, respectively), number of branches plant-1 (3.60), capsules plant-1(80.47), number of seeds capsule-1(56.02),seed yield(1.07tha-1)andharvestindex(36.46%)were observed in the variety BARI Til-4 cultivated with the application of biochar @ 6 t ha-1 (V3*B3) and the lowest one was observed in variety BARI Til-2 with no biochar application (V1*B0).Biochar is effective for increasing growth and yield of sesame. Bangladesh Agron. J. 2019, 22(2): 113-127